Enhanced dye-sensitized solar cell photocurrent and efficiency using a Y-shaped, pyrazine-containing heteroaromatic sensitizer linkage. Issue 24 (28th June 2015) - Watson, Brian L.; Sherman, Benjamin D.; Moore, Ana L.; Moore, Thomas A.; Gust, Devens
<x xml:space="preserve">Abstract</x> A new approach to dye sensitized solar cells using a pyrazine-containing linkage to join two dyes to the TiO2 photoanode enhances photovoltage, photocurrent and solar efficiency.